Triage of Limited Versus Extensive Disease on 18F-FDG PET/CT Scan in Small Cell lung Cancer - Saima Riaz; Humayun Bashir; Imran Niazi (Asia Oceania Journal of Nuclear Medicine and Biology, 2017)
Objective(s): Small cell lung cancer (SCLC) is an aggressive neuroendocrine carcinoma, which accounts for 10-15% of pulmonary cancers and exhibits early metastatic spread. This study aimed to determine the added value of 18F-FDG PET/CT imaging in tumor, node, and metastasis (TNM) staging of SCLC, compared to the conventional computed tomography (CT) scan and its potential role as a prognosticator.Methods: This retrospective review was conducted on 23 patients, who were histopathologically diagnosed to have SCLC and referred for undergoing 18F-FDG PET/CT scanning during October 2009-December 2015. The rate of agreement between the CT and 18F-FDG PET/CT findings for TNM staging was calculated using the Cohen’s kappa (κ). The median follow-up time was eight months, ranging 27-3 months). The overall and disease-free survival rates were calculated based on the extent of disease.Results: 19 cases were male and four female with the mean age of 58±9 years. The 18F-FDG PET/CT identified limited and extensive diseases in 2 (8.7%) and 21 (91.3%) patients, respectively. In addition, the results of the Cohen’s kappa demonstrated a strong (κ=0.82), fair (κ=0.24), and poor (κ=0.12) agreement between the PET/CT and CT findings for determining tumor, node, and metastasis stages, respectively. The 18F-FDG PET/CT scans upstaged disease in 47% of the cases with visceral and osseous metastasis. The disease-free survival rates for the limited and extensive diseases were 100% and 23% within the 12-month follow-up. In addition, 8 (35%) patients expired during the follow-up period.Conclusion: Improved nodal and metastatic disease identification highlights the role of 18F-FDG PET/CT scanning in initial staging of SCLC with prognostic implications.